Fertility-preserving management of post-adenomyomectomy enterocutaneous fistula with GnRH analogue - Awowole, Ibraheem O.; Olumide, Olumide A.; Adepiti, Clement A.; Akintunde, Fehintola O.; Omitinde, Oluseyi S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterocutaneous fistula is a rare pathological communication between the uterine cavity and the anterior abdominal wall, typically presenting with cyclical menstrual discharge through a cutaneous opening. While most cases occur following Caesarean sections or open myomectomy, this case describes an unusual presentation following adenomyomectomy in a 32-year-old nulligravida. The patient initially presented with symptoms suggestive of uterine fibroids but was intraoperatively found to have adenomyosis, for which adenomyomectomy with uterine reconstruction was performed. Four weeks postoperatively, she developed a localized swelling on the lower abdominal wall, which ruptured with the onset of menstruation, discharging blood through both the skin and vagina. Ultrasonography confirmed a hypoechoic tract connecting the uterus to the cutaneous swelling, consistent with uterocutaneous fistula. The patient was successfully managed non-surgically using monthly subcutaneous Goserelin injections for three months, resulting in spontaneous closure of the fistulous tract and resolution of symptoms. This case highlights the diagnostic challenges of differentiating adenomyosis from fibroids using 2D ultrasonography, as well as the importance of considering rare postoperative complications such as uterocutaneous fistula. It underscores the potential role of medical therapy with GnRH analogues as a fertility-preserving alternative to surgery in select cases, contributing to improved clinical outcomes and patient quality of life.